Reflections from the OARSI 2022 clinical trials symposium: The pain of OA—Deconstruction of pain and patient-reported outcome measures for the benefit of patients and clinical trial design - Karsdal, M.A.; Tambiah, J.; Felson, D.; Ladel, C.; Nikolov, N.P.; Hodgins, D.; Bihlet, A.R.; Neogi, T.; Baatenburg de Jong, C.; Bay-Jensen, A.C.; Baron, R.; Laslop, A.; et al. (Osteoarthritis and cartilage, 2023)
Osteoarthritis (OA) drug development is hampered by a number of challenges. One of the main challenges is the apparent discordance between pain and structure, which has had a significant impact on drug development programs and has led to hesitance among stakeholders. Since 2017, the Clinical Trials Symposium (CTS) has been hosted under the Osteoarthritis Research Society International (OARSI) leadership. OARSI and the CTS steering committee yearly invite and encourage discussions on selected special subject matter between regulators, drug developers, clinicians, clinical researchers, biomarker specialists, and basic scientists to progress drug development in the OA field. The main topic for the 2022 OARSI CTS was to elucidate the many facets of pain in OA and to enable a discussion between regulators (Food and Drug Administration (FDA) and the European Medicines Agency (EMA)) and drug developers to clarify outcomes and study designs for OA drug development. Signs or symptoms indicative of nociceptive pain occur in 50–70% of OA patients, neuropathic-like pain in 15–30% of patients, and nociplastic pain in 15–50% of patients. Weight-bearing knee pain is associated with bone marrow lesions and effusions. There are currently no simple objective functional tests whose improvements correlate with patient perceptions. The CTS participants, in collaboration with the FDA and EMA, raised several suggestions that they consider key to future clinical trials in OA including the need for more precise differentiation of pain symptoms and mechanisms, and methods to reduce placebo responses in OA trials.